Diversifikasi Pengolahan Jahe Menjadi Produk Awetan - Nami Lestari; Eldha Sampepana; Sitti Nurlina; Tita Sri Palupi (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Ginger ( Zingiber Officinale) is one of spices having many beneficial uses and its potency in East Kalimantan is quite big. This region produces about2,454.000 tons of ginger every year. (The Plantation Services of East Kalimantan Province, 2004). The aim of this research is to find an effecient technology for small and madium scale industries to process ginger to become preserved products like instant ginger drinks, candies and syrup. The research looked for the right formulae in processing of instant ginger drinks and ginger syrups and tile right filler substance in making ginger candies. The formula willbe represented in the composition of ginger, sugar and water. Based on organoleptic testing, the best species of ginger made for those products is